Empirical determination of political cultures as a basis for effective coordination of forest management systems - Pokorny, B.; Schanz, H. (2003)
To design viable strategies to implement sustainable forest management, tools are needed that allow the understanding and management of the driving forces behind conflicting opinions and divergent solutions. The approach of Thompson et al. (1990) to cultural theory—because of its descriptive power—may be an ideal basis to create such tools. The possibility of determining empirically the cultural bias of the actors and groups involved is fundamental to this approach. The authors conducted a pilot study in the eastern Amazon region to explore the possibility of characterizing individuals according to the four types of political culture defined by Thompson et al. The findings indicated that the empirical classification of individuals is possible but complex. A relation between the types of political cultures and perceptions of sustainable forest management was observed. A systematic elaboration of adequate indicators and assessment methods is crucial in exploring the potential of transferring the theoretical approach into practice.